1995
DOI: 10.1016/s0022-5223(05)80008-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of heparin concentration and activated clotting time monitoring on blood conservation

Abstract: A whole blood hemostasis system (Hepcon) provides both activated clotting time and accurate whole blood heparin concentration measurements via an automated protamine titration method. This study was designed to prospectively evaluate the impact of heparin and protamine administration using this system on the incidence and treatment of bleeding after cardiopulmonary bypass. Two hundred fifty-four patients requiring cardiopulmonary bypass were enrolled in this prospective study over a 7-month period. Patients tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
108
1
4

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 258 publications
(116 citation statements)
references
References 35 publications
3
108
1
4
Order By: Relevance
“…12,13 Using the RxDx system, we measured the heparin sensitivity and constructed individualised dose response curves for each patient. Heparin sensitivity was not different among the four patient groups, and the calculated dose of heparin using the titration was not different among the four groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Using the RxDx system, we measured the heparin sensitivity and constructed individualised dose response curves for each patient. Heparin sensitivity was not different among the four patient groups, and the calculated dose of heparin using the titration was not different among the four groups.…”
Section: Discussionmentioning
confidence: 99%
“…Despoils et al 13 demonstrated a marginally significant reduction in postoperative bleeding and reduced transfusion of non-red blood cell components using Hepcon| (Medtronic Hemotec, Parker, CO) heparin management with a transfusion algorithm. The Hepcon differs from Hemochron| RxDx instrument in that the former measures ACT and heparin concentration via an automated protamine titration technique and calculates the heparin dose required to maintain a stable heparin concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Failure to consider heparin clearance during CPB can result in significantly lower heparin concentrations during CPB that may not be reflected in lower ACT values but still gives rise to subclinical thrombin generation and factor consumption. 9 Further, since reversal of UH is achieved with protamine sulphate using an approximate ratio of 1 mg protamine to 100 IU of heparin, failure to consider heparin clearance can result in administration of significantly larger dosages of protamine than required. As protamine in its own right has anticoagulant properties, 10 excess protamine can contribute to postoperative bleeding.…”
mentioning
confidence: 99%
“…Primarily responsive to 'intrinsic' pathway activation, it can be confounded by the choice of activator (celite or kaolin), type of device, degree of hemodilution, extent of platelet activation, temperature of sample, concentration of aprotinin, and operator technique, even before considering actual alterations in hemostatic activity. 13 Several alternatives to simple celite or kaolin based ACT monitoring have been proposed, including targeting whole blood heparin concentration, 9 highdose thrombin time, plasma supplemented modified activated clotting time and an anti-Xa-activity-based coagulation assay. Despite the significant limitations of ACT monitoring including its lack of specificity and sensitivity, however, it remains the standard in many (most) centres where cardiac surgery is practiced.…”
mentioning
confidence: 99%
See 1 more Smart Citation